The Existence and Practice of Art For Children (AFC) Yogyakarta as A Non-Formal Art Education (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2018)
This article examines the existence, role, and practice of Art for Children (AFC) Yogyakarta as a community art center for children in Yogyakarta. Due to its cultural and educational setting, the children’s art center serves as an alternative for non-formal art education. The data were gathered by the passive participant observation, in-depth interview, and document review and analyzed by using the interactive model. The research results in four things. First, the establishment of the Art for Children (AFC) meets the needs of the self-actualization of both the artists and the parents in nurturing children’s art. Teaching art to children becomes the honorable way for the artists to reach his self-fulfillment as artists as well as members of a society and, on the other hand, engaging their children’s in the art center is the responsibility for the parents to fulfill their aesthetic needs and to support their children’s education. Second, the lesson emphasizes the process rather than the result; it is oriented to the development of art educational values rather than artistic skills. The training process involves collaboration between the artists and the parents. The artists engage the parents in active participation of guiding the children. Third, through this strategy the children have produced original and creative drawings and paintings worthwhile for children’s aesthetic education and cultural activity in the city.